The relationship between visual impairment and depression in low vision patients: A systematic review - Raharjo, Philipus Putra; Poli, Adelina T.; Syawal, Purnamanita; Syamsuddin, Saidah (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Visual impairment significantly impacts daily activities, quality of life, and future plans, often leading to psychological issues, including anxiety and depression. This study aims to explore the relationship between mental disorders, particularly depression, and visual impairment or low vision. Methods: A systematic literature search was conducted using online databases such as PubMed, ScienceDirect, Google Scholar, and Scopus. Search terms included combinations of keywords such as low vision, depression, psychiatric disorder, and their synonyms. The initial search yielded 362 publications, which were screened by title and abstract to identify studies that met the inclusion criteria. Nineteen articles were included in this review.Results: Low vision can affect visual function and psychosocial well-being, impairing the ability to perform daily activities. It is also closely associated with depression and other mental health issues. Individuals with low vision often experience a reduced quality of life and poorer mental health compared to those without visual impairments and may require specialist care to manage their condition.Conclusions: According to this systematic review, there is a significant correlation between depression and visual impairment.